2016
DOI: 10.1111/jfb.12877
|View full text |Cite
|
Sign up to set email alerts
|

Differential responses to environmental challenge by common carp Cyprinus carpio highlight the importance of coping style in integrative physiology

Abstract: Common carp Cyprinus carpio displaying proactive or reactive stress coping styles were acclimated to two environmental regimes (low oxygen and low temperature), and selected groups were tested for response to an inflammatory challenge (Escherichia coli lipopolysaccharide, LPS). Plasma glucose and lactate levels were measured, as were selected C. carpio-specific messenger (m)RNA transcript abundance, including cortisol receptor (CR), enolase (ENO), glyceraldehyde 3-phosphate dehydrogenase (GAPDH) and interleuki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Rey et al. (, ) also showed that proactive fish generally have an explorative behavior and a preference for higher temperature environments, when reactive animals are shyer and spent more time in lower water temperatures. Our study showed a high variability in temperature preference according to the period (before, during, and after high thermosensitive period) and the progenies.…”
Section: Discussionmentioning
confidence: 98%
“…Rey et al. (, ) also showed that proactive fish generally have an explorative behavior and a preference for higher temperature environments, when reactive animals are shyer and spent more time in lower water temperatures. Our study showed a high variability in temperature preference according to the period (before, during, and after high thermosensitive period) and the progenies.…”
Section: Discussionmentioning
confidence: 98%
“…Among the questions raised are: via what mechanisms are trait correlations inherited, which circumstances benefit different complex phenotypes, and what are the costs and benefits of the limited plasticity imposed by fixed trait associations? In the bioinformatics era, it should also be noted that understanding individual variation may be of vital importance for the interpretation of transcriptomic data [see for example Crawford and Oleksiak, 2008;MacKenzie et al, 2009;Wong et al, 2015;Rey et al, 2016].…”
Section: Neurogenesis In Fishmentioning
confidence: 99%
“…Differences in metabolism have been linked with changes in coping styles in some species (Biro and Stamps, 2008;. In relation to the stress coping style biomarkers, the literature is scarce, however some studies have been performed in fish, such as, zebrafish ), common carp (MacKenzie et al, 2009Rey et al, 2016), Nile tilapia (Oreochromis niloticus) (Vera Cruz and Brown, 2007), rainbow trout (Thomson et al, 2011) associating physiological and brain gene expression characteristics with behavioural phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…The information of these mRNAs differentially expressed between diverse SCS groups could be used for the interpretation of biological responses to resolve variation, knowing that those variations might be adaptive or genetically fixed within the population (MacKenzie et al, 2009). As commented before, the behavioural features are connected to physiological characteristics and related to this physiological association, recent molecular measurements have been associated with behavioural coping styles in response to fluctuating environmental conditions and after an inflammatory challenge in several fish species MacKenzie et al, 2009;Huntingford et al, 2010;Rey et al, 2013;Rey et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation